2005
DOI: 10.1001/archpsyc.62.3.311
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors Predicting Changes in Marijuana Involvement in Teenagers

Abstract: Assessment of substance, school, and delinquency factors is important in identifying individuals at high risk for continued involvement with marijuana. Prevention and/or intervention efforts should focus on these areas of risk.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

11
98
1
6

Year Published

2007
2007
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(117 citation statements)
references
References 77 publications
11
98
1
6
Order By: Relevance
“…Resolute nonusers reported greater parental warmth, and more intense monitoring, than vulnerable nonusers and users, who did not differ. These findings refine earlier research reporting parental differences between users and nonusers (Parker and Benson 2004;Ramirez et al 2004;van den Bree and Pickworth 2005). This same pattern emerged in analyses of adult supervision, religiosity, refusal strength, peer and self-delinquency, sensation seeking, and inhalant use.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Resolute nonusers reported greater parental warmth, and more intense monitoring, than vulnerable nonusers and users, who did not differ. These findings refine earlier research reporting parental differences between users and nonusers (Parker and Benson 2004;Ramirez et al 2004;van den Bree and Pickworth 2005). This same pattern emerged in analyses of adult supervision, religiosity, refusal strength, peer and self-delinquency, sensation seeking, and inhalant use.…”
supporting
confidence: 87%
“…This common pattern of differences among the groups also suggests that inhalant use generally anticipates marijuana use, consistent with earlier research (Johnson et al 1995;Schutz et al 1994). Reports of an inverse relationship between academic performance and drug use are common (Ellickson et al 2004;van den Bree and Pickworth 2005), and significant differences were revealed between users and nonusers in the present analyses as well. This study extends prior research by revealing that among nonusers, vulnerable respondents' academic performance was not different from that of resolute nonusers.…”
supporting
confidence: 64%
“…Finally, there is mixed evidence regarding the influence of different risk and protective factors depending upon levels of ATOD involvement such as initiation or escalation. Although most studies have found evidence that the relevance of factors varied by stage of use [26,27], other studies report little variation [25,28].…”
mentioning
confidence: 99%
“…Interestingly, Amonini and Donovan (2006) and Frank and Kendall (2001) argue that through religious teaching, desired behaviours that are linked to moral values can provide a platform for adolescents/children to make cognitive assessments when making healthy choices. Whilst empirical research into healthy behaviours indicates the efficacy between religion and desired behaviours/outcomes, the converse applies with the relationship between religion and alcohol abuse and religion and licentious sexual behaviour (Abraham, Sherran & Abraham, 1992;Bree & Pickworth, 2005;Hassett, 1981;Wallace & Bachman, 1991). Furthermore, strong negative correlations apply with the relationship between religion and drug use (Adlaf & Smart, 1985;Amonini & Donovan, 2006;Burkett & Warren, 1987;Lorch & Hughes, 1985;Lugoe & Biswalo, 1997).…”
Section: Discussionmentioning
confidence: 99%